The Significance of Photopatch Testing and Photoallergic Contact Dermatitis: 10-years experience - Sindhvananda, Jirot; Chunhasewee, Chakkrapong; Panichluechachai, Nantaporn (Journal of Health Science of Thailand, 2017)
Photopatch testing (PPT) is a standard tool to help making and confirming diagnosis of photoallergic contact dermatitis (PACD) that should correlate to patients’ history and clinical manifestation. This retrospective study reports the significance of PPT and PACD, conducted for 10 years between 2000 and 2009 at the Institute of Dermatology. Among 270 patients who completed PPT, 72 patients (26.67%) had PPT positive, but only 14/72 (19.4%) had relevant to the patients’ history and skin lesions which could make definite diagnosis as PACD. Among them, oxybenzone, a sunscreen substance was the most common causative agent (35.7%) which was corresponded with other reports, followed by promethazine hydrochloride, chlorpromazine hydrochloride, fragrance mix, triclocarban and fenticlor. Oxybenzone also caused allergic reaction in 6 cases. Data from this study would be useful for providing information relevant to the improvement of the use of PPT in the diagnosis and management of PACD and other related skin diseases, as well as the future use of data for the development of commercial products that are less harmful to the people.